FEEDING STIMULATORY EFFECTS OF CYPERUS ROTUND US TUBER ON CIRRHINUS MRIGALA - Venkateshwarlu, G.; Rambabu, M.; Patro, B.; Pal, A. K. (Journal of Indian Fisheries Association, 2015)
Traditionally tubers of cyperus (Cyperus rotundus) and its extracts havebeen used for alluring fish during harvesting in India. An experiment wasconducted to evaluate its feeding stimulatory activity and effect on the growthof a commercially important freshwater fish, Cirrhinus mrigala. Threeisonitrogenous and isocaloric formulated diets viz. plant ingredient basedcontrol and control supplemented with cyperus tuber (CS) at 1% and 5%levels were fed to the fingerlings of mrigal, Cirrhinus mrigala (2.68 + 0.20 g)for a period of 45 days. Th~ grq,wth performance and the activity of metabolicenzymes, aspartate aminotransferase (AST) and alanine aminotransferase(ALT), in liver, gill and muscle tissues of mrigal were stu!Hed during- every15 days interval. Highest relative growth (72.28%) was obtained in the mrigalfed with the diet containing 5% cyperus (5% CS), while the re!z~ti"~~e growthswere 66.18% and 43.40% for the fish fed with the 1% CS diet and controlrespectively. The activities of AST and AL T were significantly higher (p